191k views
1 vote
Urgent! Please show work!

Urgent! Please show work!-example-1
User Dvir
by
5.3k points

1 Answer

4 votes

Answer:

f(x) = x³ + x² - 22x - 40

Explanation:

Given that x = a is a zero of f(x) then (x - a) is a factor

Here the zeros are x = - 4, x = - 2, x = 5 , then the factors are

(x + 4), (x + 2) and (x - 5)

The function is then the product of the factors, that is

f(x) = (x + 4)(x + 2)(x - 5) ← expand the first pair using FOIL

= (x² + 6x + 8)(x - 5) ← distribute

= x³ + 6x² + 8x - 5x² - 30x - 40 ← collect like terms

= x³ + x² - 22x - 40

User ProjectPhysX
by
5.4k points